Force-time differences between ballistic and non-ballistic half-squats - Suchomel, T. J.; Taber, C. B.; Sole, C. J.; Stone, M. H. (Sports, 2018)
The purpose of this study was to examine the force-time differences between concentric-only half-squats (COHS) performed with ballistic (BAL) or non-ballistic (NBAL) intent across a range of loads. Eighteen resistance-trained men performed either BAL or NBAL COHS at 30%, 50%, 70%, and 90% of their one repetition maximum (1RM) COHS. Relative peak force (PF) and relative impulse from 0-50 ms (Imp50), 0-90 ms (Imp90), 0-200 ms (Imp200), and 0-250 ms (Imp250) were compared using a series of 2 × 4 (intent × load) repeated measures ANOVAs with Bonferroni post hoc tests. Cohen`s d effect sizes were calculated to provide measures of practical significance between the BAL and NBAL COHS and each load. BAL COHS produced statistically greater PF than NBAL COHS at 30% (d = 3.37), 50% (d = 2.88), 70% (d = 2.29), and 90% 1RM (d = 1.19) (all p < 0.001). Statistically significant main effect differences were found between load-averaged BAL and NBAL COHS for Imp90 (p = 0.006, d = 0.25), Imp200 (p = 0.001, d = 0.36), and Imp250 (p < 0.001, d = 0.41), but not for Imp50 (p = 0.018, d = 0.21). Considering the greater PF and impulse observed during the BAL condition, performing COHS with BAL intent may provide a favorable training stimulus compared to COHS performed with NBAL intent.